2013
DOI: 10.1139/cjc-2012-0534
|View full text |Cite
|
Sign up to set email alerts
|

A direct method for the synthesis of indolizine derivatives from easily available aromatic ketones, pyridines, and acrylonitrile derivatives

Abstract: A concise and efficient strategy has been proposed to synthesize indolizine derivatives from easily available aryl or heteroaryl methyl ketones, pyridines, and acrylonitriles. The mechanistic pathway involved the integration of iodination, pyridinium ylide synthesis, and 1,3-dipolar cycloaddition. The protocols were found to be highly efficient in terms of high yields, operational simplicity, mild reaction conditions, and easy workup. This method has provided an important supplement for the synthesis of indoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
44
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(44 citation statements)
references
References 49 publications
0
44
0
Order By: Relevance
“…Indolizines, and in particular the annulated ones, are frequently found to exhibit useful biological [ 1 , 2 , 3 , 4 , 5 , 6 ] and optical properties [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. The synthesis of indolizines usually relies on the reactivity of pyridinium ylides, which can undergo cycloaddition reactions with alkenes [ 15 , 16 , 17 , 18 ] or alkynes [ 19 , 20 , 21 , 22 , 23 ]. In some cases, interaction of ylides with alkenes or alkynes leads to a different outcome [ 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indolizines, and in particular the annulated ones, are frequently found to exhibit useful biological [ 1 , 2 , 3 , 4 , 5 , 6 ] and optical properties [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. The synthesis of indolizines usually relies on the reactivity of pyridinium ylides, which can undergo cycloaddition reactions with alkenes [ 15 , 16 , 17 , 18 ] or alkynes [ 19 , 20 , 21 , 22 , 23 ]. In some cases, interaction of ylides with alkenes or alkynes leads to a different outcome [ 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…From the view of green chemistry, using cheaper and more easily‐available methyl ketones as substrates to generate organic halides in situ in the reaction process is a more ideal choice. In 2013, Wu's group reported the synthesis of indolizines by a two‐step reaction of pyridines, aromatic methyl ketones and acrylonitrile in I 2 /CuO system (Scheme b) . Nevertheless, this reaction required 1.0 equiv.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we used a compromise scheme to further explain the reaction mechanism by using intermolecular three-components reaction of easily available 2-bromo-1-(2-hydroxyphenyl)ethan-1-one (4a) and 2-iodo-1-phenylethan-1-one (6a). 13 To our delight, under the standard conditions, 4a and 6a could react with pyridine (2a), ethyl propiolate (5a), or ethyl acrylate (7a) to get the product 3aa and indolizine derivative (8aa) (Scheme 5d,e). These results confirmed that 1aa is the potential intermediate for the cascade reaction.…”
mentioning
confidence: 99%
“…TLC was carried out on precoated glass plates. The 1 H NMR and 13 C NMR spectra were recorded on Bruker Advance 400 MHz instrument at 400 MHz ( 1 H NMR), 100 MHz ( 13 C NMR). Using the residual solvent peak in CDCl 3 as an internal reference: (δ = 7.26 for 1 H and δ = 77.0 for 13 C{ 1 H}).…”
mentioning
confidence: 99%
See 1 more Smart Citation